ISLAM DAN PANDANGAN AGAMA-AGAMA DI INDONESIA - Mahfud, Mahfud (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2021)
Islam has similarities with other theistic religions in terms of its views on the purpose of life in this world and the hereafter. That goal is part of the life of every human being and because of that humans are also competing to show humans universally about the truth of their religion. The dynamic view of Islam in providing solutions to problems faced by mankind cannot be separated from what is presented in detail in its holy book, namely the great Qur'an. Islam is a religion in which there are complete teachings with guidance as a guide for human life. its teachings are an important part of making Islam itself a blessing for the universe. Religion seen from its esoteric and exoteric dimensions has provided an open space for anyone who wants to study the study of religions. In this case, many disciplines have developed such as Christology, Islamology, Hinduism, and Buddhism. These disciplines are the right way to understand existing religions as a way to understand the religious values ​​that each religion has as our knowledge material to create a culture of peace.